Multistep Metabolic Engineering of Bacillus licheniformis To Improve Pulcherriminic Acid Production - Wang, Shiyi (Appl Environ Microbiol, 2020)
The cyclodipeptide pulcherriminic acid, produced by Bacillus licheniformis, is derived from cyclo(l-Leu–l-Leu) and possesses excellent antibacterial activities. In this study, we achieved the high-level production of pulcherriminic acid via multistep metabolic engineering of B. licheniformis DWc9n*. First, we increased leucine (Leu) supply by overexpressing the ilvBHC-leuABCD operon and ilvD, involved in Leu biosynthesis, to obtain strain W1, and the engineered strain W2 was further attained by the deletion of gene bkdAB, encoding a branched-chain α-keto acid dehydrogenase in W1. As a result, the intracellular Leu content and pulcherriminic acid yield of W2 reached 147.4 mg/g DCW (dry cell weight) and 189.9 mg/liter, which were 227.6% and 48.9% higher than those of DWc9n*, respectively. Second, strain W3 was constructed through overexpressing the leucyl-tRNA synthase gene leuS in W2, and it produced 367.7 mg/liter pulcherriminic acid. Third, the original promoter of the pulcherriminic acid synthetase cluster yvmC-cypX in W3 was replaced with a proven strong promoter, PbacA, to produce the strain W4, and its pulcherriminic acid yield was increased to 507.4 mg/liter. Finally, pulcherriminic acid secretion was strengthened via overexpressing the transporter gene yvmA in W4, resulting in the W4/pHY-yvmA strain, which yielded 556.1 mg/liter pulcherriminic acid, increased by 337.8% compared to DWc9n*, which is currently the highest pulcherriminic acid yield to the best of our knowledge. Taken together, we provided an efficient strategy for enhancing pulcherriminic acid production, which could apply to the high-level production of other cyclodipeptides. IMPORTANCE Pulcherriminic acid is a cyclodipeptide derived from cyclo(l-Leu–l-Leu), which shares the same iron chelation group with hydroxamate sidephores. Generally, pulcherriminic acid-producing strains could be the perfect candidates for antibacterial and anti-plant-pathogenic fungal agents. In this study, we obtained the promising W4/pHY-yvmA pulcherriminic acid-producing strain via a multistep metabolic modification. The engineered W4/pHY-yvmA strain is able to achieve 556.1 mg/liter pulcherriminic acid production, which is the highest yield so far to the best of our knowledge.